2014
DOI: 10.1111/dote.12229
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eosinophilic esophagitis in a United States military health-care population

Abstract: Eosinophilic esophagitis (EoE) is a rapidly emerging chronic immune-mediated condition affecting children and adults, both genders, and all races. A large variation in the prevalence of EoE exists in the literature. The aim of this study is to establish the prevalence of EoE in a military health-care population in the United States using a comprehensive electronic medical record search. Using the International Classification for Diseases-9 code for EoE (530.13), the total number of EoE patients enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
0
34
0
4
Order By: Relevance
“…In our study, we estimated the prevalence in children (under 18 yrs of age) to be 25.1/100,000. In the adult population (18–65 yrs of age), we estimated the prevalence of EoE at 30/100,000, while previous studies in literature have reported prevalence rates ranging from 9.5–56.7/100,000 [6,7,8,12,15,16,17]. Multiple factors likely contribute to the variation in prevalence rates among studies, some of which include methods of data collection, data analyses, case definition of EoE and regional variation of EoE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we estimated the prevalence in children (under 18 yrs of age) to be 25.1/100,000. In the adult population (18–65 yrs of age), we estimated the prevalence of EoE at 30/100,000, while previous studies in literature have reported prevalence rates ranging from 9.5–56.7/100,000 [6,7,8,12,15,16,17]. Multiple factors likely contribute to the variation in prevalence rates among studies, some of which include methods of data collection, data analyses, case definition of EoE and regional variation of EoE.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been three recent epidemiological studies in EoE [7,16,17] utilizing large databases, we added previous proton-pump inhibitor (PPI) exposure to the case definition of EoE to exclude cases of PPI-responsive esophageal eosinophilia (PPI-REE) [1,18], to make our estimate of prevalence more precise. We sought to describe the epidemiology of EoE in the United States (US), and identify associated disorders by using a population-based database.…”
Section: Background and Aimsmentioning
confidence: 99%
“…13,14 A study in the U.S. military found a prevalence of 10/100,000, but this might have been an underestimate due to the specialized population assessed or to low sensitivity of the administrative code for EoE. 66,69 Studies from the Netherlands and the southern region of Denmark have also reported lower prevalences of EoE. 21,64 It is unknown if these results are due to practice patterns in those countries or a true difference in the prevalence of disease.…”
Section: Prevalencementioning
confidence: 99%
“…Nevertheless, a number of investigators have used a variety of strategies to report prevalence estimates ranging from less than 10 to more than 80 cases per 100,000. 5-15 The potential for estimating EoE prevalence at the national level was made possible in 2008 with the approval of an International Classification of Diseases, Ninth Revision (ICD-9) code for EoE (530.13). We have recently validated this code for use in administrative database research, and found that the specificity of the code was extremely high.…”
Section: Introductionmentioning
confidence: 99%